Breeding season of the hermit crab petrochirus diogenes (anomura : diogenidae) in the north coast of São Paulo state, Brazil - Bertini, G. (2002)
Petrochirus diogenes, one of the largest hermit crabs in the western Atlantic, was studied in the north coast of the State of São Paulo, Brazil, to determine its breeding season through the analysis of gonad development at a macroscopic level. The analysis of 999 crabs collected from 1995 to 1999, based on four categories of gonad development, showed that males present gonads in the advanced stage during all seasons, and although females present developed ovaries all year as well, the peak incidence is in the summer. The peak of recruitment occurs in the winter.